Part I. Choose exactly one question (Question 1 or Question 2) in this part to answer.
g(0) = 1; g(1) = 3; and
g(n) = g(n - 1) + 2 g(n - 2) - 2n + 5, for all n ³ 2.
Prove by induction that g(n) = 2n + n for all n ³ 0.
Solution:
Prove by induction on n ³ 0 that
g(n) = 2n + n.
(Basic Step) Consider the cases of n = 0 and n = 1:
In the case that n = 0: Using the formula, g(0) = 20 + 0 = 1 + 0 = 1, which is equal to the
initial value defined for g(0).
In the case that n = 1: Using the formula, g(1) = 21 + 1 = 2 + 1 = 3, which is equal to the
initial value defined for g(1).
Thus, the formula for g(n) is correct for n = 0 and n = 1.
(Induction Hypothesis) Suppose the formula g(n) = 2n + n is correct for all n in the range
0 £ n £ k, for some k ³ 1.
(Induction Step) Consider n = k + 1. We need to prove g(k+1) = 2k+1 + (k+1) -------(1)
Note that g(k+1) = g(k+1- 1) + 2g(k+1- 2) – 2(k+1) + 5, by applying the recurrence to
g(k+1), since k + 1 ³ 1 + 1 = 2.
= g(k) + 2g(k- 1) – 2k – 2 + 5
= (2k + k) + 2(2k- 1+ k- 1) – 2k + 3, by applying the induction hypothesis to
g(k) and g(k- 1)
= 2k + k + 2k + 2k – 2 – 2k + 3
= 2(2k) + k + 1
= 2k+1 + k + 1
= RHS of (1)
Thus, the induction step is proved. By induction, we proved g(n) = 2n + n for all n ³ 0.
Solution: We use induction on n ³ 1.
(Basic Step) Consider n = 1.
(Induction Hypothesis) Consider n = k.
(Induction Step) Consider n = k+1. We need to prove
Note that (3) is true because (k + 2)2 > (k + 2)(k +1).
Thus, the induction step is proved. By induction, we proved the problem.
Part II. Choose exactly one question (Question 3 or Question 4) in this part to answer.
Solution:
(a) In order to prove R Ì S, let (x, y) Î R ----(1), we need to prove (x, y) Î S ----(2).
Since R Ç S defines a function from A to B, there exists a pair (x, z) Î R Ç S ----(3) for some z Î B; that is, for xÎ A, the function R Ç S maps x to z Î B. From (3), (x, z) Î R Ç S Ì R.
Thus, both (x, y) Î R, from (1), and (x, z) Î R. However, R defines a function from A to B by assumption; thus, x must be mapped under R to a unique element in B, i.e. y = z. Therefore,
(x, y) = (x, z) Î R Ç S, by (3)
Ì S, by the definition of Ç .
Thus, (2) is proved.
Since R defines a function from A to B, R maps x to some element z Î B, i.e., (x, z) Î R --(6)
Therefore, (x, y) Î S Ì R È S and (x, z) Î R Ì R È S. Since R È S defines a function from A to B, it maps x to a unique element in B, i.e., y = z. Therefore, (x, y) = (x, z) Î R, by (6).
Thus, (5) is proved.
Prove by induction that g(anb) = b2, for all n ³ 1.
Solution:
We use induction on n ³ 1 to prove g(anb) = b2.
(Basic Step) When n = 1. In this case,
g(anb) = g(ab)
= g(abl ), because ab = abl
= bg(bl ), Rule (5)
= bbg(l ), Rule (3)
= b2l , Rule (1)
= b2, because b2l = b2.
Thus, the Basis step is proved.
(Induction Hypothesis) Consider n = k.
Assume g(akb) = b2 for some k ³ 1.
(Induction Step) Consider n = k + 1. We need to prove g(ak+1b) = b2 ----(1)
Note that g(ak+1b) = g(aaak- 1b), since k ³ 1 so k + 1 ³ 2
= g(aak- 1b), Rule (4) with u= ak- 1b
= g(akb)
= b2, by the I.H.
Thus, the induction step is proved. By induction, we proved g(anb) = b2 for all n ³ 1.